A Study On Tungsten-Copper Composites Produced Via Combination Of Liquid Phase Sintering And Liquid Infiltration Techniques - Ahmed, Hafed Ibrahim Ihmida (2014)

(untitled)
The low solubility between W and Cu elements makes it difficult to attain full density using the conventional sintering methods. In this work a unique method has been proposed to fabricate the W-Cu system, achieving excellent composite properties. The proposed new method combines the liquid phase sintering and liquid infiltration and is named as the Copper-Melt Infiltration (Cu-MI) method. Base element powders of tungsten (W) and copper (Cu) and the additive elements of nickel (Ni), cobalt (Co) and iron (Fe) were used in this study. The additive elements were used as sintering activator in the range of 0.3-3 wt. %. The elemental powders were mixed manually in alumina mortar for 30 minute to produce composite powders. Thereafter, the mixture powder was compacted under different pressure (150-600MPa) and isothermally sintered at different temperature (1050, 1150 and 1250°C) as well as different atmosphere (vacuum, mixture of hydrogen and argon gas, pure argon gas and pure hydrogen gas). In the development of sintering approach, full density (>99% of theoretical density) of the sintered compact was achieved at low sintering temperature of 1150°C under hydrogen gas as protective furnace environment compared with low sintering density (not more than 89% of theoretical density) of the same sintered compact prepared by conventional liquid phase sintering. Using hydrogen gas as protective furnace environment gave the best outcome compared with others environment furnace. The electrical conductivity and hardness were enhanced using copper-melt infiltration method to fabricate the W-Cu green compact. Furthermore, Cu-MI consolidation method was employed to identify the advantages over conventional liquid phase sintering.